Facies analysis of the Uppermost Kubang Pasu Formation, Perlis: a wave-and storm-influenced coastal depositional system - Meor Hakif Amir Hassan; Yeow, Boon Sim; Lee, Chai Peng; Abdul Hadi Abdul Rahman (Universiti Kebangsaan Malaysia, 2013)
A detailed sedimentological study and facies analysis of the Permian age, uppermost succession of the Kubang Pasu Formation in Perlis was conducted in order to reconstruct the palaeo-depositional environment. Four stratigraphic sections of the uppermost Kubang Pasu Formation were logged at Bukit Chondong and Bukit Tungku Lembu, Perlis. The sections were divided into facies based on lithology and sedimentary structures. Large scale patterns in the form of facies associations and facies successions were also identified. The uppermost Kubang Pasu Formation can be divided into several coarsening upward facies successions. Each facies succession grades upward from an offshore facies association (FA1) composed of bioturbated mudstone and minor thin sandstone, into a distal lower shoreface facies association (FA 2) composed primarily of mudstone interbedded with hummocky cross-stratified sandstone (HCS) and finally a proximal lower shoreface facies association (FA 3) composed of amalgamated hummocky cross-stratified sandstone beds. The facies succession is interpreted as representing a wave- and storm-influenced coastal depositional environment. The gradual transition from siliciclastics to carbonates is probably related to post rift thermal subsidence and tectonic quiescence due to separation of Sibumasu from Gondwana during the Permian.